Diagnostic framing of IgM monoclonal gammopathy: Focus on Waldenström macroglobulinemia. Issue 2 (7th September 2018) - Tedeschi, Alessandra; Conticello, Concetta; Rizzi, Rita; Benevolo, Giulia; Laurenti, Luca; Petrucci, Maria Teresa; Zaja, Francesco; Varettoni, Marzia
Abstract: The finding of an IgM monoclonal gammopathy often represents a diagnostic challenge. In fact, there are many pathological disorders associated with this condition, each of which has distinctive characteristics and requires specific clinical, instrumental, and laboratory assessments to set the appropriate treatment. This review has two aims. Firstly, to provide a framework of the broad spectrum of IgM‐associated disorders: (1) monoclonal gammopathy of undetermined significance (MGUS); (2) Waldenström macroglobulinemia (WM); (3) IgM‐related disorders (among which hyperviscosity syndrome, light chain amyloidosis, cold agglutinin disease, cryoglobulinaemia, IgM neuropathy, Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, skin changes (POEMS) syndrome, Castleman disease); (4) IgM‐secreting multiple myeloma (IgM‐MM); and (5) other lymphoproliferative disorders which may be associated with IgM (such as chronic lymphocytic leukemia, small lymphocytic lymphoma, and B‐cell non Hodgkin lymphoma). Secondly, to give a detailed insight regarding diagnosis and treatment of WM.